E-Learning and Teaching Methods: Towards New Innovative Practices - Benfarha, Mohamed; Sefian Lamarti, Mohammed; Khaldi, Mohamed (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
In recent years, due to the rapid development of information and communication technologies, online education has grown exponentially, opening up new perspectives in the field of education, but it faces many challenges related to learner engagement, retention and quality of learning. E-learning has become a widely adopted learning method worldwide. In this context, innovative pedagogical methods play an essential role, offering teaching methods adapted to the needs of today's learners. This study focuses on innovative pedagogical methods in the context of online education. In this study, we explore several innovative pedagogical methods using digital technologies (gamification, microlearning, personalization, machine learning, virtual reality integration, etc.). We explore how these approaches are implemented, their benefits and how they can overcome traditional barriers to online teaching. Our findings highlight the benefits of these approaches in terms of learner engagement, enhancing the overall learner experience.